Answer:
4
Explanation:
[TeX] a_1=8,a_7=0[/TeX]
Since the third term is the sum of the two previous terms
[TeX] a_3=a_2+a_1[/TeX]
[TeX] a_7=a_6+a_5[/TeX]
[TeX] a_7=a_5+a_4+a_4+a_3[/TeX]
Continuing in like manner
[TeX] a_7=5a_3+3a_2[/TeX]
Since [TeX] a_3=a_2+a_1[/TeX]
[TeX] a_7=5(a_2+a_1+3a_2[/TeX]
[TeX] a_7=5a_2+5a_1+3a_2[/TeX]
[TeX] a_7=8a_2+5a_1[/TeX]
Recall: [TeX] a_1=8,a_7=0[/TeX]
[TeX] 0=8a_2+5*8[/TeX]
[TeX] 8a_2=-40[/TeX]
[TeX] a_2=-5[/TeX]
The sequence is therefore:
8,-5,3,-2,1,-1,0
The sum of the seven numbers is 4.